Virtual Network Embedding for Evolving Networks - Zhiping Cai; Fang Liu; Nong Xiao; Qiang Liu; Zhiying Wang (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
Network virtualization has been proposed as a powerful vehicle for running multiple customized networks on a shared infrastructure. Virtual network embedding is a critical step for network virtualization that deals with efficient mapping of virtual nodes and virtual links onto the substrate network resources. Previous work in virtual network embedding primarily focused on designing heuristic algorithms for static networks. Virtual network infrastructure should be reconfigured or redeployed in response to network growth. In this paper, we address the problem of optimally redeploying the existing virtual network infrastructure as the network evolves. This problem focus on minimizing the upgrading cost of virtual network, with satisfying node resource constraint and path delay constraint. It is shown that this problem is NP-hard. A heuristic algorithm is proposed and its effectiveness is validated by simulations evaluation.